ANALISIS KERJA SAMA SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN PROJECT BASED LEARNING - Dahlan, Taufiqulloh; Iskandar, Dadang; Harmaen, Deni; Noerafifah, Hani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
The purpose of this study is to describe the following: 1) The concept of the Project Based Learning model in increasing the cooperation ability of elementary school students; 2) Project Based Learning model strategy to improve elementary school student cooperation skills; 3) Cooperation between elementary school students with the Project Based Learning model. This study used a qualitative descriptive analysis with the type of literature study research or literature study). Sources of data used are primary and secondary data sources obtained from various sources of journals, books, theses, which have previously conducted research on the Project Based Learning model to improve the collaboration skills of elementary school students. Based on the results of the analysis of various journals using the Project Based Learning model there is an increase. Because, the Project Based Learning model is a learning model that gives students the freedom to build their own knowledge through problem solving activities carried out by the investigation process, gathering information to complete a project work carried out collaboratively or collaboratively and being able to produce a useful product. Tujuan dari penelitian ini adalah untuk mendeskripsikan mengenai: 1) Konsep model Project Based Learning dalam meningkatkan kemampuan kerja sama siswa Sekolah Dasar; 2) Strategi model Project Based Learning untuk meningkatkan kemampuan kerja sama siswa Sekolah Dasar; 3) Hubungan kerja sama siswa Sekolah Dasar dengan model Project Based Learning. Penelitian ini menggunakan analisis deskriptif kualitatif dengan jenis penelitian studi pustaka atau studi literatur). Sumber data yang digunakan menggunakan sumber data primer dan sekunder yang diperoleh dari berbagai sumber jurnal, buku, skripsi yang sebelumya telah melakukan penelitian mengenai model Project Based Learning untuk meningkatkan kemampuan kerja sama siswa Sekolah Dasar. Berdasarkan hasil analisis dari berbagai jurnal yang menggunakan model Project Based Learning terdapat peningkatan. Karena, model Project Based Learning merupakan suatu model pembelajaran yang memberi kebebasan siswa dalam membangun pengetahuannya sendiri melalui kegiatan pemecahan masalah yang dilakukan dengan proses penyelidikan, pengumpulan informasi untuk menyelesaikan suatu pengerjaan proyek yang dilakukan secara kolaboratif atau kerja sama dan mampu menghasilkan suatu produk yang bermanfaat.